Assessment of fasted and fed gastrointestinal contraction frequencies in healthy subjects using continuously tagged MRI. Issue 2 (11th December 2019) - de Jonge, Catharina S.; Sprengers, André M. J.; van Rijn, Kyra L.; Nederveen, Aart J.; Stoker, Jaap
Abstract: Background: Continuously tagged MRI during free breathing can assess bowel motility at frequencies as low as the slow wave, motility pattern range. This study aimed to evaluate noninvasive gastrointestinal‐tagged MRI for small bowel motility assessment and to observe the physiological response to a 300‐kcal meal challenge in healthy, overnight‐fasted volunteers. Methods: After overnight fasting, 16 healthy subjects (7 women, mean age 25.5, range 19‐37 years) underwent a free breathing, tagged MRI scan to capture small bowel motility. Each subject underwent a (a) baseline motility scan, (b) food challenge, (c) postchallenge scan, and (d) second postchallenge scan (after 20 minutes). Motility was quantified using a frequency analysis technique for measuring the spectral power of the strain, referred to as motility score. Motility score was assessed in 20 frequency intervals between 1 and 20 contractions per minute (cpm), and the data were analyzed with linear mixed‐effect models. Key Result: The stimulation protocol demonstrated an immediate, food‐induced, motility response in the low‐frequency range (2‐10 cpm), which is consistent with the stomach and small bowel frequency range (3‐12 cpm). Conclusions and Inferences: This study shows that this MRI tagging technique is able to quantify the fasted‐to‐fed response to a 300‐kcal meal challenge within the specific small bowel motility frequency range in healthy subjects. The food provocation MRI protocol provides a tool to explore the gut's response to a stimulus in specific motility frequency ranges in patients with gastrointestinal dysmotility and functional disorders. Abstract : In this study, we evaluate the noninvasive gastrointestinal tagged MRI scan and frequency analysis method for motility assessment with a food‐stimulation protocol in fasted healthy volunteers. The stimulation protocol demonstrated an immediate, food‐induced, motility response that manifested in the gastric and small intestinal frequency range. Tagged MRI has the potential to provide insights into the underlying processes of gastrointestinal motility.